To solve the system of equations using the elimination method, we have:
- \( y = x^2 + 10 \)
- \( y = -7x - 2 \)
First, we can set the two equations for \( y \) equal to each other:
\[ x^2 + 10 = -7x - 2 \]
Next, we rearrange the equation to bring all terms to one side:
\[ x^2 + 7x + 10 + 2 = 0 \]
This simplifies to:
\[ x^2 + 7x + 12 = 0 \]
Now, we will factor the quadratic:
\[ (x + 3)(x + 4) = 0 \]
Setting each factor to zero gives us the values of \( x \):
- \( x + 3 = 0 \) → \( x = -3 \)
- \( x + 4 = 0 \) → \( x = -4 \)
Now that we have the \( x \)-values, we can substitute them back into one of the original equations to find the corresponding \( y \)-values. We'll use \( y = -7x - 2 \) for this purpose.
For \( x = -3 \):
\[ y = -7(-3) - 2 = 21 - 2 = 19 \] Thus, one solution is \( (-3, 19) \).
For \( x = -4 \):
\[ y = -7(-4) - 2 = 28 - 2 = 26 \] Thus, the other solution is \( (-4, 26) \).
So the solutions to the system of equations are:
- \( (-3, 19) \)
- \( (-4, 26) \)
The correct response is:
(−3,19) and (−4,26)